Huruf “Ba” dalam Bahasa Arab dan Implikasinya Terhadap Penafsiran Ayat Al-Qur’an / The Letter "Ba" in Arabic and Its Implications on The Interpretation of The Al-Qur'an Verse) - Djuaeni, M Napis; Mahmud, Basri; Hamzah, Hamzah (Diwan: Jurnal Bahasa dan Sastra Arab, 2021)
يهدف هذا البحث إلى الكشف عن معانى حرف الباء باعتباره الحرف الثاني في الأبجدية العربية، وتضمينه على تفسير آية القرآن. ويعتبر هذا البحث من البحوث الوصفية النوعية، نوعه من حيث الموقع فهو البحث المكتبي الذي بياناته تعتمد على الكتب المرجعية والمجلات ونتائج البحوث المتعلقة بموضوع البحث مباشرة. والبيانات التي تم الحصول عليها تتم معالجتها بشكل تفاعلي عن طريق تخفيض البيانات حسب الحاجة وعرض البيانات ثم أخيرا التحقق من البيانات واستخلاص النتيجة إما بشكل استقرائي أو استنتاجي. ونتائجه تشير إلى أن حرف الباء (ب) في اللغة العربية له معاني متنوعة بلغ مجموعه 14 معنى، وهي: 1) الإلصاق، 2) التعدية، 3) الإستعانة، 4) السببية، 5) المصاحبة والملابسة، 6) الظرفية، 7) البدل، 8) المقابلة (العواض)، 9) المجاوزة، 10) الإستعلاء، 11) التبعيض، 12) القسم، 13) الغاية، و14) الزائدة. وأما تضمينه على تنوع معني حرف الباء فإنه يؤدي إلى ظهور تفسيرات مختلفة لآيات القرآن كما في حالة سورة المائدة/5:6. الكلمات المفتاحية: حرف الباء; اللسانيات العربية; تفسير القرآن Abstract: This study aims to explore the meaning of the letter ba as the second letter in the Arabic alphabet and its implications for the interpretation of the al-Qur'an verse. This research is included in descriptive qualitative research. In terms of location, it is a type of library research which relies on direct data from reference books, journals and research results related to the researcher's theme. The resulting data is processed interactively by reducing the data as needed, and starting to compile it (data display), then finally verifying the data and drawing a conclusion (data verification and conclution) either inductively or deductively. The results of this study indicate that the letter ba in Arabic has a variety of meanings totaling 14 meanings, namely: 1) al-ilshaq, 2) al-ta'diyah, 3) al-istianah, 4) al-sababiyah, 5) al. -musahabah wa al-mulabasah, 6) al-dzarfiyah, 7) al-badal, 8) al-muqabalah (al-'iwadh), 9) al-mujawazah, 10) al-isti'la ', 11) al- tab'idh, 12) al-qasam, 13) al-ghayah, and 14) al-zaidah (al-taukid). The implications of the diversity of meanings of the letter ba, it gives rise to different interpretations of the verses of the al-Qur'an, such as the case in the QS. al-Maidah / 5: 6.